2022
DOI: 10.1186/s12984-022-00988-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing motor cortex activation during grasping via novel robotic mirror hand therapy: a pilot fNIRS study

Abstract: Background Mirror therapy (MT) has been used for functional recovery of the affected hand by providing the mirrored image of the unaffected hand movement, which induces neural activation of the cortical hemisphere contralateral to the affected hand. Recently, many wearable robots assisting the movement of the hand have been developed, and several studies have proposed robotic mirror therapy (RMT) that uses a robot to provide mirrored movements of the unaffected hand to the affected hand with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…However, most of these devices are designed for shoulder, elbow, or wrist movements ( 25 , 28 ), there are few rehabilitation robots for the hand, such as the fingers. For robot-assisted BMT (RBMT) in the hand, Chen et al and Dong et al developed a task-oriented training protocol that uses an exoskeleton hand to perform RBMT ( 29 , 30 ). A functional brain imaging study on RBMT reported that, compared with unilateral hand movement, robot-assisted bilateral hand movement induced greater excitatory responses in the motor cortex ( 30 ), suggesting the clinical effectiveness of RBMT.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these devices are designed for shoulder, elbow, or wrist movements ( 25 , 28 ), there are few rehabilitation robots for the hand, such as the fingers. For robot-assisted BMT (RBMT) in the hand, Chen et al and Dong et al developed a task-oriented training protocol that uses an exoskeleton hand to perform RBMT ( 29 , 30 ). A functional brain imaging study on RBMT reported that, compared with unilateral hand movement, robot-assisted bilateral hand movement induced greater excitatory responses in the motor cortex ( 30 ), suggesting the clinical effectiveness of RBMT.…”
Section: Introductionmentioning
confidence: 99%
“…But even shorter robotic proprioceptive training can modulate plasticity in stroke patients (Vahdat et al, 2019). Kim et al (2022) also demonstrated greater neural stimulation on the contralateral side of the motor cortex through bilateral robot-assisted training. Overall, both methods, mirror illusion and sensory input, show positive characteristics that are successfully combined in RMT.…”
Section: Discussionmentioning
confidence: 99%
“…They have the potential to improve the quality and intensity of rehabilitation treatments (Morone et al, 2020). Only few studies have investigated RMT so far (Beom et al, 2016;Kim et al, 2022). However, they have included mainly healthy people or patients with moderate upper limb impairment.…”
Section: Introductionmentioning
confidence: 99%
“…fNIRS has also been used to study cortical activation in patients with stroke. For example, Kim used fNIRS to study the oxy-Hb changes in patients with stroke in robotic mirror therapy to observe the efficacy of the therapy (39). Mihara also used fNIRS to study cortical activation differences between patients with stroke and healthy peers during ataxia gait (40).…”
Section: Introductionmentioning
confidence: 99%